Atrial fibrillation progression and the importance of early treatment for improving clinical outcomes. (6th June 2022) - Gunawardene, Melanie A; Willems, Stephan
Abstract: Over time, atrial fibrillation (AF) naturally progresses from initially paroxysmal to persistent/permanent AF caused by structural and electrical remodelling with a complex underlying pathogenesis. It has been demonstrated that this progression of AF itself is linked to negative cardiovascular outcomes (stroke, systemic embolism, and hospitalization due to heart failure). Consequently, there is a profound rationale for early treatment of AF as a cornerstone of AF management. Recent randomized trials produced evidence that early rhythm control is effective in maintaining sinus rhythm, lower the risk of cardiovascular outcomes, and that catheter ablation of AF is effective to delay AF progression. This review will illuminate current evidence regarding the hypothesis of early AF treatment to prevent AF progression and improve clinical outcomes.